The Influence of Psychological Behavior on Employee Outcomes with Mediating Variables of Working Culture, Safety Climate, Workplace Environment, Leader Style, Working Discipline and Moderating Working Endurance: Systematic Literature Review - Rusman Rusman; Supardi Supardi (Dinasti Publisher, 2026)
This article synthesizes a literature review on the influence of psychological behavior on employee outcomes, considering the roles of working culture, safety climate, workplace environment, working discipline, and working endurance. The study employed a library research approach and a Systematic Literature Review (SLR) based on a review of national and international journals, academic books, and relevant scientific documents from 2020–2026. The analysis process included descriptive analysis, content analysis, bibliometric analysis, thematic analysis, and gap analysis. The results indicate that psychological behavior is related to motivation, work engagement, job attitude, stress response, commitment, and psychological resilience. Furthermore, working culture, safety climate, workplace environment, Leader Style and working discipline emerge as organizational mechanisms that shape work behavior and strengthen employee outcomes. Working endurance plays a crucial moderating role because employees' physical and mental abilities influence performance resilience under work pressure. This article emphasizes that previous research is still partial and has not integrated all variables into a comprehensive conceptual model. Therefore, this article produces a new conceptual framework and hypothetical directions for further research.